2003
DOI: 10.1016/s0006-3495(03)75034-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of the NGF-TrkA Domain 5 Complex and Comparison with Biological Data

Abstract: The nerve growth factor (NGF) is an important pharmacological target for Alzheimer's and other neurodegenerative diseases. Its action derives partly from its binding to the tyrosine kinase A receptor (TrkA). Here we study energetics and dynamics of the NGF-TrkA complex by carrying out multinanosecond molecular dynamics simulations, accompanied by electrostatic calculations based on the Poisson-Boltzmann equation. Our calculations, which are based on the x-ray structure of the complex, suggest that some of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 38 publications
2
30
0
Order By: Relevance
“…In these regards, the N-terminal domain of NGF has been disclosed as essential for the stability of the NGF/TrkA complex (Berrera et al, 2006), where the formation of H-bonds at the protein−protein interface stabilized the functional NGF/TrkA-D5 binding (Settanni et al, 2003). …”
Section: Discussionmentioning
confidence: 99%
“…In these regards, the N-terminal domain of NGF has been disclosed as essential for the stability of the NGF/TrkA complex (Berrera et al, 2006), where the formation of H-bonds at the protein−protein interface stabilized the functional NGF/TrkA-D5 binding (Settanni et al, 2003). …”
Section: Discussionmentioning
confidence: 99%
“…2). Settanni et al identified a key role for the residues lying at the ligand-receptor interface [136]. These include His4, Glu11, Trp 21, Arg 59, Arg103 of NGF, Glu 295, Phe 303, Arg347, Asn 349, and Gln 350 of TrkA receptor [136,137].…”
Section: Binding Details Of Copper(ii) and Zinc(ii) Interaction With Ngfmentioning
confidence: 99%
“…Settanni et al identified a key role for the residues lying at the ligand-receptor interface [136]. These include His4, Glu11, Trp 21, Arg 59, Arg103 of NGF, Glu 295, Phe 303, Arg347, Asn 349, and Gln 350 of TrkA receptor [136,137]. In particular, the His 4 and Glu 11 residues provide highly persistent H-bond interactions with the receptor, as well as Ile 6 and Phe 7 residues stabilize the binding of the N-term of NGF to TrkA through hydrophobic interactions [137].…”
Section: Binding Details Of Copper(ii) and Zinc(ii) Interaction With Ngfmentioning
confidence: 99%
See 1 more Smart Citation
“…Only in the hNGF/TrkA complex (Wiesmann et al, 1999; Wehrman et al, 2007) and in one of the two protomers of a complex with a DNA aptamer (Jarvis et al, 2015), is the N-terminus defined and folded in an α-helix. The generally accepted view is thus that the N-terminus is disordered in the NGF unbound state (Settanni et al, 2003; Berrera et al, 2006). Similar conclusions have been recently reached as result of CD and NMR solution studies and molecular dynamics simulations on two linear hNGF N-terminus peptides (Stanzione et al, 2010; Travaglia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%